Issues And Juristic Opinions On The Investment Of Waqf Funds: An Overview From The Endowment Fund Of Kelantan Endowment Committee - Abdulsoma Thoarlim; Mohammed Muneer’deen O.A.; Asyraf Hj Ab Rahman; Bedjo Santoso; Mohamad Zaharuddin Zakaria (Fakultas Ekonomi, Universiti Islam Sultan Agung, 2024)
Volume: 17 No: 2